Domain I of 23S rRNA competes with a paused transcription complex for ribosomal protein L4 of Escherichia coli. - Zengel, J M (1993)
Ribosomal protein L4 of Escherichia coli regulates expression of its own eleven gene S10 operon both by inhibiting translation and by stimulating premature termination of transcription. Both regulatory processes presumably involve L4 recognition of the S10 leader RNA. To help define L4's regulatory target, we have investigated the protein's cognate target on 23S rRNA. Binding of L4 to various fragments of the 23S rRNA was monitored by determining their ability to sequester L4 in an in vitro transcription system and thereby eliminate the protein's effect on transcription. Using this approach we identified a region of about 110 bases within domain I of 23S rRNA which binds L4. A two base deletion within this region, close to the base to which L4 has been cross-linked in intact 50S subunits, eliminates L4 binding. These results also confirm the prediction of the autogenous control model, that L4 bound to its target on rRNA is not active in regulating transcription of the S10 operon.